Physico-chemical characteristics and microbial profile “in natura” of goat milk from the region of Jaguaretama, Ceará, Brazil (Research, Society and Development, 2023)
Caprine farming has experienced remarkable growth in recent years, especially in the Northeast region of Brazil. In this area, historical and geoclimatic factors have played a crucial role in the success of caprine farming, making it a standout on the national stage. Goat's milk, with its richness in fat and nutrients, serves as an excellent raw material for the production of dairy derivatives. Therefore, the analysis its quality holds significant importance in ensuring the excellence of derived products. The objective of this research was to assess the microbiological and physicochemical quality “in natura” of goat milk from Jaguaretama, Ceará, Brazil. Ten raw goat milk samples were collected from various producers in the municipality of Jaguaretama-Ceará, Brazil. The microbiological and physicochemical parameters of these samples were analyzed in the Milk Technology Laboratory of the Federal Institute of Education, Science, and Technology of Ceará (IFCE), situated on the Limoeiro do Norte campus, CE. All samples in this study complied with the physicochemical parameters and thermotolerant Coliforms. However, a single sample exceeded the regulatory limits for total Coliforms, highlighting the need to enhance hygiene practices during milk production, transportation, and storage. It is crucial to emphasize the importance of adhering to good management and hygiene practices in milk production to ensure quality and safety. Maintaining high hygiene standards at all stages of the process is essential to meet regulations and meet the expectations of consumers seeking safe and nutritious dairy products.